Mechanical Properties Analysis of Polypropylene Biocomposites Reinforced with Curaua Fiber - Bispo,Sistanley Jones Lima (2015)
Over the last few years, great interest has been shown by researchers in presenting alternative proposals for the design and fabrication of materials with good mechanical properties and low cost for a variety of applications. With this in mind, a study was carried out on the addition of curaua fibers in a polypropylene (PP) matrix. These were extruded in the pellets form with curaua fiber content of 5, 10 and 20% (mass percentage). An injector was used to make the test specimens from these pellets, which were then subjected to mechanical tests (tensile and three point bending), physical and thermal tests (fluidity index and HDT). As a consequence, it was noted that the incorporation of fibers in composites of PP with curaua resulted in an increase in the elastic modulus and tensile strength improving therefore the mechanical properties of these materials. Another important point was to check if there was an increase in heat deflection temperature as the fibers were added. As a result, it has been found that it is feasible to use these materials in industry, facilitating its recycling and improving its final mechanical properties.